A Three-Phase Linear Power Flow Calculation Method for Distribution Networks Considering PV Nodes - Kuan LIU; Chun WANG; Fagen YIN; Yujie CHEN; Huicheng WU (Zhongguo dianli)
In order to meet the needs of rapid analysis of distribution system, a three-phase linear power flow calculation method is proposed in this paper for distribution networks with PV nodes. According to the characteristics of the distribution networks, the nonlinear terms in the node power equation in the form of polar coordinates are linearly approximated. And a linear node power equation is obtained by using the properties of the admittance matrix to simplify the node power equation. Based on the linear node power equation, a three-phase linear power flow calculation model is established for the distribution networks considering PV nodes, which not only considers the PV nodes, but also applies to the weak-loop distribution networks, and has a strong universality. Finally, using the calculation results of Newton-Raphson method as a benchmark, a case study is made on a 33-bus distribution system, and the results show that the calculation error of the proposed method meets the requirements for rapid analysis of the distribution system. Compared with the existing linear power flow calculation method, the proposed method has higher accuracy.